المحددات التنظيمية للإبداع الإداري داخل المؤسسة - برقوق, عبد الرجمان ،; لبوز, الباحث: إلياس (Sciences de l'Homme et de la Société; Vol. 19 (2016): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ)
يمثل الإبداع الإداري النهضة الإدارية الحديثة، لكونه يعتبر الطريق السالك لهذه المنظمات من أجل التحقيق المؤكد لأهدافها، والهدف المشترك لهذه المؤسسات المختلفة هو تحقيق الاستمرارية، وهذه الأخيرة لا تتأتى إلى عن طريق التطوير الدائم للآليات المختلفة لهذه المؤسسات، كما تعد مرونة عملية الإبداع الإداري من الأسباب التي جعلت من المؤسسات تتخذه منهجًا لها، فالإبداع الإداري لا يملك أسلوبًا خاصًا أو تقنيات جبرية تقتضي تنفيذها من أجل تحقيقه، وقياسًا عليه تم وضع مجموعة من المحددات التنظيمية التي يمكن للأشخاص قياس ومعرفة تواجد الإبداع الإداري ومدى شدته وكيفية تمييزه عن غيره من الأساليب الإدارية الأخرى وملامسة مؤشراته الدالة عليه. Abstract : The administrative creativity is a modern management of the Renaissance, to be considered paved the way for these organizations to certainly investigate its objectives, and the common goal of these institutions is to ensure continuity, and it comes not by the continued development of the different mechanisms of these institutions, as is the flexibility of the reasons innovation management processes for which the institutions take the approach, Administrative creativity has no particular method or algebraic techniques needed to implement to achieve, and compared it was a set of regulatory determinants that people can see and measure the presence of administrative creativity and gravity and how to distinguish it from the situation in other administrative and other indices color touch function.